Charge-Sharing SAR ADCs for Low-Voltage Low-Power Applications - Rabuske, Taimur; Fernandes, Jorge (Analog Circuits and Signal Processing, 2017)
This book introduces readers to the potential of charge-sharing (CS) successive approximation register (SAR) analog-to-digital converters (ADCs), while providing extensive analysis of the factors that limit the performance of the CS topology. The authors present guidelines and useful techniques for mitigating the limitations of the architecture, while focusing on the implementation under restricted power budgets and voltage supplies.